3D geological model-based hydraulic fracturing parameters optimization using geology–engineering integration of a shale gas reservoir: A case study. (November 2022) - Liu, Yuyang; Ma, Xinhua; Zhang, Xiaowei; Guo, Wei; Kang, Lixia; Yu, Rongze; Sun, Yuping
Abstract: Tremendous reserves of shale gas resources exhibit broad development prospects in southern Sichuan, China. "Horizontal well + hydraulic fracturing" is taken as the principal means of shale gas reservoirs development. The design of hydraulic fracturing parameters is of great importance for the formation and extension of artificial fractures. With Well Area X of the shale gas reservoir from the Ordovician Wufeng Formation to the Silurian Longmaxi Formation in Luzhou, southern Sichuan, China, as an example. This paper identifies the artificial fracture-related characterization parameters, presents a detailed portrayal of the spatial characteristics of the fracture network, and optimizes the 4 key parameters of fracturing construction (i.e., injection rate, cluster spacing, fluid injection intensity, and proppant injection intensity) based on the geology–engineering integration fracturing simulation by building a regional 3D geological model. The result suggests that optimal injection rate, optimal cluster spacing, optimal fluid injection intensity, and optimal proppant injection intensity exist under certain geological characteristic parameters. According to the 3D geological model and simulation results of the study area, the optimal injection rate, optimal cluster spacing, optimal fluid injection intensity, and optimal proppant injection intensity are 14 m 3 /min, 10 m, 30 m 3 /m, and 2.5 t/m, respectively. The 3D geological model-based method for optimizing the fracturing parameters of shale gas reservoirs using geology–engineering integration can also applies to identifying the optimal fracturing parameters of other shale gas or tight oil well areas.